(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
Cloud computing is named as the conveyance of computing overhauls above the Web. Today many characters make utilization of cloud computing services for their very own needs. Cloud computing system is accessed using network which provides software, hardware, processing power etc. to the user when demand is generated. Cloud Computing is a virtual pool of computing resources which provides the pool to users through internet. Cloud Computing provides various services to user by creating group of clusters and grids of computers. The main goal behind this is to provide services in virtualized manner to reduce burden of user to maintain everything by itself. It also refers to the web-based computing which provides devices with shared pool of resources, information or software on demand and pay per-use basis. Instead of having local servers or own devices to manage applications, people use sharing computing resources model of Cloud. The Cloud computing provides a numerous advantages to its users but at the dark side it’s also suffers from lots of issues like Integrity or Storage Correctness, Availability, Confidentiality and more.